Risk factors for Developing Diabetes Mellitus amongst Diabetic Patients Attending at the Chittagong Diabetes Hospital Complex (Bangladesh Journal of Nutrition, 2012)
No abstract available DOI: http://dx.doi.org/10.3329/bjnut.v22i0.12829 Bangladesh Journal of Nutrition Vol.22-23 2009-2010 pp.31-40